1997
DOI: 10.1007/s00282-997-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Is treatment with hydroxyurea leukemogenic in patients with essential thrombocythemia? An analysis of three new cases of leukaemic transformation and review of the literature

Abstract: From 1981 to 1995, we diagnosed, followed and treated at our institution fifty-eight cases of essential thrombocythemia (ET), using hydroxyurea (HU) as first-line therapy in these patients. Three patients who were continuously receiving HU had a leukemic transformation after a chronic phase of respectively 47, 81 and 90 months. One patient developed an acute leukemia with minimal myeloid differentiation (AML MO) and soon died of refractory disease; the second developed a refractory anemia with excess blasts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…6,7 Recently, it has also been reported that long-term treatment with HU may favor an evolution of ET into MDS/AML, 8 marked by a 17p deletion (17p−) with loss of one TP53 allele, vacuolated neutrophils and presentation of the Pelger-Huét anomaly. Even if this reported association still needs to be proved, 18,19 four of our eight AMLs having evolved from ET occurred in subjects treated with HU and three of them developed a 17p−. In every case FISH with the p53 DNA probe detected only one red signal, confirming loss of one TP53 allele.…”
Section: Discussionmentioning
confidence: 82%
“…6,7 Recently, it has also been reported that long-term treatment with HU may favor an evolution of ET into MDS/AML, 8 marked by a 17p deletion (17p−) with loss of one TP53 allele, vacuolated neutrophils and presentation of the Pelger-Huét anomaly. Even if this reported association still needs to be proved, 18,19 four of our eight AMLs having evolved from ET occurred in subjects treated with HU and three of them developed a 17p−. In every case FISH with the p53 DNA probe detected only one red signal, confirming loss of one TP53 allele.…”
Section: Discussionmentioning
confidence: 82%
“…However, opinion experts have remained divided concerning the true leukemogenic potential of HU for this patient population [17,[20][21][22][23][24]; thus uncertainty remains today [25]. In a clinical trial of HU therapy for children and young adults with SCD, there were no cases of leukemia with a mean follow-up observation time of 3 years [26].…”
Section: Discussionmentioning
confidence: 99%
“…The neoplastic clones in CMPDs are able to differentiate into the cell lines that predominate the chronic phase but also into other lineages in the blastic phases of disease. Thus, in ET, in which the megakaryocytes and platelet production dominate the chronic phase, most secondary leukemias were of myeloid differentiation [7,8,10,11]. In only a few patients, ET evolved into megakaryoblastic leukemia [8,11,12].…”
Section: Introductionmentioning
confidence: 99%